The composition effect on the bowing parameter in the cubic InGaN, AlGaN and AlInN alloys - Berrah, S.; Boukortt, A.; Abid, A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Numerical simulation based on FP-LAPW calculations is applied to study direct and indirect band gap energy of the cubic AlxGa₁₋xN, InxGa₁₋xN and InxAl₁₋xN alloys.The direct and indirect band-gap bowing parameter is also calculated, and the values obtained are very important, as we find a strong dependence of the bowing parameter on the composition.